Employment and Educational Equivalence Outcomes as Measures of Employment and Career Counselling - Conger, Stuart; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2008)
In Canada, government departments and other funders of services tend to view change in employment status as the primary indicator of success in career and employment counselling. If a client becomes employed, the counselling is viewed as successful, whileall other outcomes are viewed as failures. We advance the idea that many other outcomes, such as seeking further training, can result in increased financial productivity over the long term, and therefore an employment equivalence measurement can be developed to depict this outcome. Furthermore, employment equivalence can interact with factors such as increased salary resulting from further training to yield a measure of return on investment that provides an indication of the financial return on some counselling outcomesthat do not produce an immediate change in employment status. Numerous examples are provided to illustrate how employment equivalence and return on investment can be used to demonstrate the value of career development services.